2021
DOI: 10.12669/pjms.38.icon-2022.5776
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of in-hospital cardiac arrest in a Pakistani tertiary care hospital pre- and during COVID-19 pandemic

Abstract: Objectives: To determine epidemiology of in-hospital cardiac arrest (IHCA) in a tertiary care hospital, pre- and during pandemic. Methods: This is a cross-sectional study of inpatients who experienced an in-hospital-cardiac arrest at a tertiary care hospital in Karachi between August 2019 and August 2020. Outcome variables were return of spontaneous circulation (ROSC) and survival to discharge (StD) and analysis was also done comparing pre- and during pandemic period. Results: A total of 77 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Of the remaining studies, another 23 were excluded because they were reviews, case reports, or not in English. Finally, the 11 included manuscripts [26][27][28][29][30][31][32][33][34][35][36] referring to 10 studies were included in the meta-analysis. Girotra et al [28] and Gupta et al [29] refer to the same population, however, Girotra et al [28] analyze the IHCA for positive and negative COVID-19 pandemic patients, while Gupta et al [29] compare the periods before and during the COVID-19 pandemic.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining studies, another 23 were excluded because they were reviews, case reports, or not in English. Finally, the 11 included manuscripts [26][27][28][29][30][31][32][33][34][35][36] referring to 10 studies were included in the meta-analysis. Girotra et al [28] and Gupta et al [29] refer to the same population, however, Girotra et al [28] analyze the IHCA for positive and negative COVID-19 pandemic patients, while Gupta et al [29] compare the periods before and during the COVID-19 pandemic.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies included in the meta-analysis were published between 2020 -2022, and the countries included the USA, UK, Sweden, Singapore, Pakistan, Germany and China. Among those studies, eight reported IHCA outcomes between the prepandemic and COVID-19 pandemic periods (95,115 vs. 27,633 patients, respectively) [26,27,29,[32][33][34][35], and three studies during the COVID-19 period among SARS-CoV-2 positive vs. negative patients (6,225 vs. 20,401 patients, respectively) [28,30,34,36]. The baseline characteristics are described in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…Survival to discharge ranges from 18-28% in hospitals (de Visser et al, 2019;Schluep et al, 2018). In Pakistan, only 1 in 100 people survive cardiac arrest (Ahmed et al, 2022). Cardiac arrests without hospital admission have a survival to discharge of approximately 10% (Myat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%